2009
DOI: 10.1111/j.1547-5069.2009.01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Knowledge of Blood‐Borne Pathogens and Avoidance of Contact With Infected Patients

Abstract: Our study indicated some reluctance among nurses to care for patients with blood-borne pathogens. This appears to be the result of value systems and not a lack of knowledge, indicating a need to integrate a psychoeducational approach to education of nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 39 publications
1
14
1
7
Order By: Relevance
“…This is most probably because the full-time students are more aware of HCV infection risks than the part-time students. In Israel, the percentage of nurses who shun contact (77.3 %) with HIV, HBV, and HCV infected patients is much higher (15), but this may mostly be related to the fear of HIV/AIDS (17). These results however confi rm that HCV patients are stigmatised (18)(19)(20)(21) and that this kind of intolerance leads adversely affects the quality of patient care (22).…”
Section: Knowledge About Hcv Infectioncontrasting
confidence: 43%
See 2 more Smart Citations
“…This is most probably because the full-time students are more aware of HCV infection risks than the part-time students. In Israel, the percentage of nurses who shun contact (77.3 %) with HIV, HBV, and HCV infected patients is much higher (15), but this may mostly be related to the fear of HIV/AIDS (17). These results however confi rm that HCV patients are stigmatised (18)(19)(20)(21) and that this kind of intolerance leads adversely affects the quality of patient care (22).…”
Section: Knowledge About Hcv Infectioncontrasting
confidence: 43%
“…A research conducted in Israel showed a high level of knowledge among 180 nurses about blood-borne infections and better knowledge of HBV than HCV infection (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in conformity with the results posted by [18] which essentially means the educational program addressed some knowledge gaps identified in the Standard Precautions. However, another study [19] demonstrated a contrary result which infers that there could be other factors other than knowledge that determines of compliance to the Standard Precautions.…”
Section: The Self-reported Compliance With the Standard Precautionsmentioning
confidence: 76%
“…It is the absence of verbal, physical, and social contact with patients, including lack of eye contact, decreased physical proximity, decreased time spent with the patient, and negative verbal mannerisms (Siminoff, Erlen, & Sereika, 1998). Nurses' avoidance behavior has been reported in various studies (Gutierrez, 2005;Healy & McKay, 2000;Kagan, Ovadia, & Kaneti, 2009;Lambert, Lambert, Petrini, Li, & Zhang, 2007;Mackintosh, 2007;Röndahl, Innala, & Carlsson, 2003;Tyson & Pongruengphant, 1996;Wong, Leung, & So,2001) and has been associated with repeated exposure to morally distressing situations (Gutierrez, 2005).…”
Section: Avoidance Thoughts and Behaviorsmentioning
confidence: 99%